Thar Kavi : a new pumpkin variety - Raja, S; Yadav, Lalu Prasad; Singh, Sanjay; Sharma, B D (Indian Horticulture, 2019)
Thar Kavi, a new high-yielding cultivar of pumpkin, has been developed at Central Horticultural Experiment Station, Vejalpur, Gujarat. Released by the Central Institute for Arid Horticulture, Bikaner, in 2016, the superior phenotype has been bred by hybridization followed by selection from the segregating population of CM16 Ã— CM19. It has medium vigorous plant having mediumsized leaves with prominent white patches. Each plant produces about 7-9 fruits, weighing each at 800-900g. Fruits are flat round, dark green with greenish lines at flower end of the fruits. The ripe fruit flesh is of deep orange with rich carotene. Fruits mature in 110-120 days. It is moderately resistant to pumpkin mosaic virus disease at field condition. It is best suited for rainfed hot, semiarid and arid ecosystem.